Emotional intelligence in Spanish elite athletes: Is there a differential factor between sports? - Mon-Lopez, D.; Blanco-Garcia, C.; Acebes-Sanchez, J.; Rodriguez-Romo, G.; Marquina, M.; Martin-Castellanos, A.; De la Rubia, A.; Cordente Martinez, C.; Mallen, J. O.; Garrido-Munoz, M. (Sports, 2023)
Emotional intelligence is a determinant factor in sports performance. The present study analysed differences in total emotional intelligence and its four dimensions in 2166 Spanish athletes (25.20 ± 10.17 years) from eight sports (volleyball, track and field, shooting, football, basketball, handball, gymnastics, and judo). A total of 1200 men and 966 women answered anonymously using a Google Forms questionnaire sent via WhatsApp about demographics and psychological variables. A Pearson correlation was conducted to assess the age-emotional intelligence relationship. An independent T-test and One-Way ANOVA were carried out to check for age differences between biological sex and sport and a One-Way ANCOVA to determine differences between sports controlled by age. Age differences were observed by sex and sport (p < 0.001). An association was found between age and emotional intelligence dimensions (p < 0.001), except for other`s emotional appraisal (p > 0.05). Judo was the sport with the highest levels of regulation of emotions, other`s emotional appraisal, use of emotion, and total emotional intelligence (p < 0.05). Generally, emotional intelligence was found to be more developed in individual sports than in team sports, except football. Consequently, psychological skills like emotional intelligence could be critical to achieving high performance, depending on the sport.